Marine species distribution shifts on the U.S. Northeast Continental Shelf under continued ocean warming - Kleisner, Kristin M.; Fogarty, Michael J.; McGee, Sally; Hare, Jonathan A.; Moret, Skye; Perretti, Charles T.; Saba, Vincent S. (Progress in oceanography, 2017)
•Future changes in suitable thermal habitat for marine species on the U.S. NE Shelf.•Increasing ocean temperatures results in northward shifts for many species.•Potentially major changes in species complex in different regions of the Shelf.•Species may shift from one management jurisdiction to another.•Shifts of marine taxa may substantially effect local fishing communities.•Changes will depend on the pace of climate change and species’ adaptability. The U.S. Northeast Continental Shelf marine ecosystem has warmed much faster than the global ocean and it is expected that this enhanced warming will continue through this century. Complex bathymetry and ocean circulation in this region have contributed to biases in global climate model simulations of the Shelf waters. Increasing the resolution of these models results in reductions in the bias of future climate change projections and indicates greater warming than suggested by coarse resolution climate projections. Here, we used a high-resolution global climate model and historical observations of species distributions from a trawl survey to examine changes in the future distribution of suitable thermal habitat for various demersal and pelagic species on the Shelf. Along the southern portion of the shelf (Mid-Atlantic Bight and Georges Bank), a projected 4.1°C (surface) to 5.0°C (bottom) warming of ocean temperature from current conditions results in a northward shift of the thermal habitat for the majority of species. While some southern species like butterfish and black sea bass are projected to have moderate losses in suitable thermal habitat, there are potentially significant increases for many species including summer flounder, striped bass, and Atlantic croaker. In the north, in the Gulf of Maine, a projected 3.7°C (surface) to 3.9°C (bottom) warming from current conditions results in substantial reductions in suitable thermal habitat such that species currently inhabiting this region may not remain in these waters under continued warming. We project a loss in suitable thermal habitat for key northern species including Acadian redfish, American plaice, Atlantic cod, haddock, and thorney skate, but potential gains for some species including spiny dogfish and American lobster. We illustrate how changes in suitable thermal habitat of important commercially fished species may impact local fishing communities and potentially impact major fishing ports along the U.S. Northeast Shelf. Given the complications of multiple drivers including species interactions and fishing pressure, it is difficult to predict exactly how species will shift. However, observations of species distribution shifts in the historical record under ocean warming suggest that temperature will play a primary role in influencing how species fare. Our results provide critical information on the potential for suitable thermal habitat on the U.S. Northeast Shelf for demersal species in the region, and may contribute to the development of ecosystem-based fisheries management strategies in response to climate change.